Методи електромагнітного тестування та діагностики радіоантен покоління 5G - Бондарчук, В. К.; Мацуй, А. М.; Каліч, В. М.; Bondarchuk, V.; Matsui, A.; Kalich, V. (ЦНТУ, 2025)
Виконано огляд ключових технологій телекомунікаційних бездротових систем п’ятого покоління, особливості яких вимагають зміни в підходах до тестування радіо компонентів. Зроблено порівняльний огляд сучасних підходів до після виробничого неінвазійного тестування активних антенних систем та можливостей використання елементів машинного навчання для підвищення ефективності виявлення дефектів. The purpose of this article is to review the key elements of fifth-generation (5G) wireless systems and the methods used for electromagnetic testing and defect detection of active antenna systems. Due to the introduction of massive MIMO technologies and millimeter-wave (mmWave) communication in 5G networks, traditional testing approaches are no longer effective, prompting the need for new non-invasive methods. The article aims to analyze current approaches to post-production non-invasive testing of active antenna systems and explore the potential of machine learning elements to enhance the efficiency of defect detection.
Analysis of Electromagnetic Testing and Defect Detection Tools for 5G Generation Radio Antennas
Keywords: 5G; електромагнітне тестування; OTA; машинне навчання; виявлення дефектів; electromagnetic testing; OTA testing; machine learning; defect detection